2015
DOI: 10.1097/sla.0000000000001420
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Genotype Determines Phenotype and Disease-related Outcomes in Thyroid Cancer

Abstract: Objectives To correlate thyroid cancer genotype with histology and outcomes. Background The prognostic significance of molecular signature in thyroid cancer (TC) is undefined but can potentially change surgical management. Methods We reviewed a consecutive series of 1510 patients who had initial thyroidectomy for TC with routine testing for BRAF, RAS, RET/PTC, and PAX8/PPARG alterations. Histologic metastatic or recurrent TC was tracked for 6 or more months after oncologic thyroidectomy. Results Papillar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
80
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 112 publications
(96 citation statements)
references
References 29 publications
6
80
0
3
Order By: Relevance
“…The same variants also displayed a higher OR for fvPTC compared with cPTC. Of note, fvPTC was recently reported to be associated with infrequent ETE and lymph node metastases (31). This finding coincides with the data showing stronger association of rs116909374 and rs944289 with fvPTC and, at the same time, a negative association with lymph node and distant metastases.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The same variants also displayed a higher OR for fvPTC compared with cPTC. Of note, fvPTC was recently reported to be associated with infrequent ETE and lymph node metastases (31). This finding coincides with the data showing stronger association of rs116909374 and rs944289 with fvPTC and, at the same time, a negative association with lymph node and distant metastases.…”
Section: Discussionsupporting
confidence: 81%
“…Several reports have shown that a somatic mutation in BRAF V600E is associated with a higher recurrence rate in PTC and may be useful in predicting the risk of metastases. In a recent publication, 1510 patients with thyroid cancer (97% had PTC) underwent routine molecular testing for BRAF, RAS, RET/PTC, and PAX8/PPARG alterations with postsurgical follow-up tracking metastases and recurrence of the disease (31). It was shown that BRAF V600E -positive PTC cases have a higher metastatic rate, while RAS-positive cases are predominately fvPTC with infrequent ETE and lymph node metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…In follicular-cell derived thyroid carcinoma RET mutations are generally rare events [41]. In a previous report RET gene variations were found in 1/22 (4.5%) ATC investigated [5].…”
Section: Discussionmentioning
confidence: 99%
“…10 Most RAS mutations have correlated to histologically low-grade FVPTC, but they also occur in other cancer types including FTC, poorly differentiated, and anaplastic thyroid cancer, and even medullary thyroid cancer. 9,11,12 …”
mentioning
confidence: 99%